Partial Hydrogenation of FAME on Trickle Bed Reactor using Nickel Catalyst - Teguh Budi Santoso; Yuswan Muharam (Fluida, 2022)
FAME (fatty acid methyl ester) is an alternative fuel that is still limited in its application to engines because its low oxidation stability affects the quality of biodiesel storage. A solution to overcome this problem is the partial hydrogenation process in which polyunsaturated FAMEs react with hydrogen, and a catalyst breaks down unsaturated bonds which are oxidation determinants. The use of Ni/Al2O3 catalyst is more advantageous due to its lower cost and higher activity. In this research, partial hydrogenation was carried out in a trickle-bed reactor. The objective of the research is to investigate the effect of operating conditions on FAME conversion. The experimental result shows that the partial hydrogenation of polyunsaturated FAMEs in a trickle bed reactor broke down the polyunsaturated bonds (C19:2) of FAME’s into monounsaturated bonds (C19:1) and saturated bonds (C19:0). The conversion of polyunsaturated FAMEs reaches 8.93% under the inlet pressure of 0.7 MPa, the inlet temperature of 160°C, the hydrogen flowrate of 250 ml/min, the biodiesel flowrate of 0.667 ml/min, and the catalyst size of 1.5 mm.